Familial colon cancer: Gastrojejunocolic fistula - Fronzutti, Agustín; Cazabán, Luis A.; Segura, Juan; Oehninger, Carlos (Cirugía del Uruguay, 1977)
Two brothers presented, simultaneously, colonic adenocancer complicated by digestive fistula, without prior neoplasic lesions. A study of their genealogy showed a family history with high cancer incidence. It is only by establishing the genetic makeu of such families that it is possible to diagnose this type of cancer and indicate adequate treatment.